Study on Property and Mechanism of Adsorption of Chlorogenic Acids by Zinc-Containing D401 Macroporous Resin - Xuan, Han; Xie, Fazhi; Wang, Ying; Cao, Tian; Chen, Yan; Xia, Binbin (Asian Journal of Chemistry, 2014)
The property and mechanism of the adsorption of chlorogenic acids by zinc-containing D401 macroporous adsorption resin was analyzed. The isothermal adsorption property, the kinetic characteristics, the dynamic adsorption and desorption characteristics of the adsorption of chlorogenic acids by zinc-containing D401 macroporous resin were investigated by the adsorption test. The results indicate that the equilibrium time of adsorption is 2 h. The adsorption follow the second-order kinetic equation with the adsorption rate constant 0.0024 g mg-1 h-1; the adsorption isotherm data correspond well to the Langmuir equation with the maximum adsorption capacity (Qm) 43.10 mg g-1 and the adsorption is a physical adsorption. The adsorption flow rate is 2 BV/h; the solution concentration is 1.3 mg/mL and pH value is 1. The adsorbed chlorogenic acids can be eluted from zinc-containing D401 macroporous resin by 70 % ethanol.